End-to-side neurorrhaphy of the sural nerve to the superficial fibular nerve: An anatomically feasible technique for restoring sensation following sural nerve harvest - Khadanovich, Anhelina; Benes, Michal; Kaiser, Radek; Giele, Henk; Kachlik, David (Journal of plastic, reconstructive & aesthetic surgery, 2025)
The sural nerve is commonly used as an autologous nerve graft. Its harvest results in a sensory deficit in the corresponding distribution area. End-to-side neurorrhaphy of the distal sural nerve stump to the superficial fibular nerve could address the problem of sensory loss in the dorsolateral foot without altering the donor nerve. The purpose of our study is to elaborate on a technique for sural nerve-to-superficial fibular nerve end-to-side neurorrhaphy. Fourteen legs from seven formaldehyde-preserved cadavers were dissected. The sural nerve was transected two centimeters above the distal tip of the lateral malleolus (LM) and mobilised to reach the intermediate dorsal cutaneous nerve (IDCN) and the medial dorsal cutaneous nerve (MDCN). The measurements were taken to localise the coaptation points with the nerves. The distal stump of the sural nerve had to be mobilised 18.0 (8.6-24.9) mm distally in relation to the distal tip of LM in order to reach the IDCN. The coaptation point with the IDCN was 18.9 (15.3-22.8) mm above the distal tip of the LM on the anterior margin of the LM. Mobilisation of 33.7 (25.5-38.8) mm was required for reaching the MDCN. The coaptation point with the MDCN was 19.9 (15.8-27.0) mm above the distal tip of the LM, overlaying the lateral margin of the extensor digitorum longus muscle. The end-to-side neurorrhaphy of the sural nerve to the superficial fibular nerve is anatomically feasible and can be performed on both IDCN and MDCN. We recommend using the MDCN due to its larger diameter.
Keywords: Sural nerve graft; End-to-side neurorrhaphy; Sural nerve; Superficial fibular nerve